EFEKTIVITAS KANTOR URUSAN AGAMA (KUA) DALAM PEMBUATAN AKTA IKRAR WAKAF DI KECAMATAN MAMAJANG KOTA MAKASSAR - Anggriani, Emi; Amin, Muhmmadiyah; Alimuddin (Universitas Islam Negeri Alauddin Makassar, 2025)
Abstract This study discusses the effectiveness of the Religious Affairs Office (KUA) in making waqf pledge deeds in Mamajang District, Makassar City. What the author explores is how the Religious Affairs Office (KUA) in Mamajang District, Makassar City acts as a PPAIW and how the management of the Religious Affairs Office (KUA) in Mamajang District, Makassar City in making waqf pledge deeds. The type of research used is field research using qualitative methods. With the main source of this research is data in the field as the main source such as observation, interviews and documentation. The results of this study reveal that the KUA in Mamajang District acts as a PPAIW which is described into four, namely, the KUA acts as a verifier, facilitator, educator, and mediator. The management of the KUA in Mamajan District in making waqf pledge deeds so far out of 11 waqf assets, only 2 waqf assets have been made into waqf pledge deeds. The KUA in Mamajang District has not been effective in issuing waqf pledge deeds, this is due to, 1) The absence of a certificate of ownership of waqf property, 2) The deceased Wakif, and 3) Lack of public awareness. The need for understanding to provide valuable insights in the development of religious and legal knowledge, especially about waqf. Support the KUA in Mamajang District in conducting more active socialization to increase public understanding of waqf. Keywords: Deed of waqf Pledge, Effectiviness, KUA